Rapid Gardos Hereditary Xerocytosis Diagnosis in 8 Families Using Reticulocyte Indices - Picard, Véronique; Guitton, Corinne; Mansour-Hendili, Lamisse; Jondeau, Bernard; Bendélac, Laurence; Denguir, Maha; Demagny, Julien; Proulle, Valérie; Galactéros, Frédéric; Garçon, Loic (Frontiers in Physiology, 2021)
Gardos channelopathy (Gardos-HX) or type 2 stomatocytosis/xerocytosis is a hereditary hemolytic anemia due to mutations in the KCNN4 gene. It is rarer than inherited type 1 xerocytosis due to PIEZO1 mutations (Piezo1-HX) and its diagnosis is difficult given the absence of a specific clinical or biological phenotype. We report here that this diagnosis can be sped up using red blood cell (RBC) indices performed on an ADVIA 2120 (Siemens®) analyzer, which measures reticulocyte mean corpuscular volume (rMCV) and mean corpuscular hemoglobin concentration (rMCHC). We studied reticulocyte indices in 3 new and 12 described patients (8 families) with Gardos-HX, 11 subjects presented the recurrent p.Arg352His mutation, 4 cases (two families) carried a private KCNN4 mutation. They were compared to 79 described patients (49 families) with Piezo1-HX. Surprisingly, in Gardos-HX cases, rMCV revealed to be smaller than MCV and rMCHC higher than MCHC, in contrast with normal or Piezo1-HX RBC. Consequently, ΔMCV (rMCV-MCV) was −0.9 ± 5 fL vs. 19.8 ± 3 fL (p < 0.001) in Gardos compared with Piezo1-HX and ΔMCHC (rMCHC-MCHC) was 18.7 ± 13 vs. −50 ± 8.7 g/L (p < 0.001). A threshold of 8.6 fL for ΔMCV and −5.5 g/L for ΔMCHC could discriminate between Gardos and Piezo1-HX with 100% sensitivity and specificity, regardless of age, mutation or splenectomy status. Consequently, we showed that reticulocytes indices are useful to suggest Gardos-HX on blood count results, allowing to rapidly target these patients for gene analysis. In addition, these parameters may prove useful as a ‘functional tool’ in interpreting new KCNN4 variants.